A Study on the Level of Job Competencies Possessed by the Employees of a Consultancy Organization - Kasilingam, R.; Riasudeen, S. (Gyan Management Journal, 2012)
Companies redefine their work culture in order to be more customers responsive, with a fine balance on employee performance. The core values of an enterprise can be met by high performance standards and degree of excellence that act as behavioural indicators in a competitive global environment. Competency mapping is a HR tool that integrates the human resource system in an organization. This research is conducted among the employees US based consultancy organisation. Around 150 employees were surveyed in order to identify the skill possessed by them. Most of the employees feel that they possess the required skill. But actually there exist a big gap between expectation from HR department and what actually possessed by them. The gap is mainly because people do not know what is expected from them.